2003
DOI: 10.1161/01.str.0000044165.41303.50
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a Statistical Model to Predict Stroke Outcome in the Context of a Large, Simple, Randomized, Controlled Trial of Feeding

Abstract: Background and Purpose-Statistical models to predict the outcome of stroke patients have several uses. Their utility depends on their predictive accuracy in patients other than those on whom they were developed (ie, external validity). We sought to test the external validity of some recently described models in patients enrolled in the FOOD (Feed Or Ordinary Diet) trial: a large randomized trial evaluating feeding policies in patients with stroke. Methods-The predictive variables were collected during a teleph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…In the Oxfordshire Community Stroke Project [22, 25], which is the only externally validated predictive model, pre-stroke independence, and normal Glasgow Coma Scale verbal score, arm power, and ability to walk were significant predictors of survival free of dependency at 6 months, whereas increasing age and living alone were associated with a poorer outcome for this parameter. In the Perth Community Stroke Study, the major predictor of new disability at 5 years was recurrent stroke (odds ratio = 12.4, 95% CI 3.3–63); other independent predictors were increasing age and stroke severity [26].…”
Section: Predictive Factors For Stroke Prognosismentioning
confidence: 99%
“…In the Oxfordshire Community Stroke Project [22, 25], which is the only externally validated predictive model, pre-stroke independence, and normal Glasgow Coma Scale verbal score, arm power, and ability to walk were significant predictors of survival free of dependency at 6 months, whereas increasing age and living alone were associated with a poorer outcome for this parameter. In the Perth Community Stroke Study, the major predictor of new disability at 5 years was recurrent stroke (odds ratio = 12.4, 95% CI 3.3–63); other independent predictors were increasing age and stroke severity [26].…”
Section: Predictive Factors For Stroke Prognosismentioning
confidence: 99%
“…Both these models have been individually validated in several studies [ 11 16 ]; see Table 2 . However, their relative performance has received little attention.…”
Section: Introductionmentioning
confidence: 99%
“…There is no cut-off to determine what constitutes an acceptable C statistic although, as the C statistic is identical to the area under a receiver operating curve for a dichotomous outcome, a value of 0.5 indicates the model is no better than chance [12]. …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown C statistics for the prediction of 6-month post-stroke independent survival (OHS ≤2) with the SSV model of between 0.79 and 0.84 [6,12,13,14]. …”
Section: Discussionmentioning
confidence: 99%